Relationship between CEO characteristics, ownership concentration and speed of adjustment on leverage in selected Asian countries - Chua, Mei Shan (2019)
Awareness of recapitalisation transaction costs in capital structure decisions has led to the introduction of dynamic capital structure. Since then, academicians have investigated the average speed of adjustment towards target leverage and their findings revealed that the speed varied across firms, industries, countries, and years. Hence, they analysed the determinants of the heterogeneous speeds. Nevertheless, the true nature of the determinants is yet to be revealed. To fill the research gap, this study examined the determinants of the speed of adjustment towards target leverage from the upper echelons perspective. Firstly, this study estimated the average speed of adjustment. Next, the impact of chief executive officers’ (CEOs’) characteristics on the speed of adjustment towards target leverage was investigated, followed by the effect of ownership concentration on the speed of adjustment towards target leverage. Finally, this study analysed the moderating effect of ownership concentration on the relationship between CEOs’ characteristics and speed of adjustment towards target leverage. To conduct the analysis, the two-step System Generalised Method of Moments (SYS-GMM) was employed, with samples from ASIAN countries, specifically ASEAN (Malaysia, Singapore, Indonesia, and Thailand) from 2007 to 2017. For pooled full sample, this study affirmed that ASEAN firms were under-adjusted towards the target leverage. Furthermore, this study revealed that CEOs’ education level improved the speed of adjustment while their age and experience impaired it. In addition, this study exposed the efficient monitoring tasks of large shareholders on the speed of adjustment, whereby they exerted their influence over older and more experienced CEOs in adjusting more quickly towards the target leverage. Based on the cross-country analysis, this research revealed a heterogeneous average speed of adjustment across the countries. Moreover, this study discovered the importance of CEOs in defining the speed of adjustment decisions for each country. Not only that, this research also unveiled the role of large shareholders in solving (Malaysian and Singaporean firms) or exacerbating (Indonesian and Thai firms) CEOs’ entrenchment behaviour in adjusting towards the target leverage. Furthermore, large shareholders were revealed to exercise their voting rights based on the amount of readjustment transaction costs. One of the implications of the findings is the financial markets can provide more financing choices to ASEAN countries for the improvement of underadjusted financing behaviour. Besides that, CEOs shall acquire more knowledge and skills that reduce the risk aversion behaviour towards the speed of adjustment. For the benefit of shareholders’ wealth, large shareholders may have to exercise their voting rights to enforce decisions that maximise the return from their investment. This study contributes to the capital structure in several ways. It serves as a platform to explicitly communicate the determinants of the Dynamic Capital Structure (Speed of Adjustment towards target leverage) based on the Upper Echelons Theory (UET) (CEOs’ Age, Education, and Experience) and Agency Theory (AT) (Ownership Concentration). Additionally, the findings have added to the literature on the role of managerial competency (individualism) within collectivist culture in making the firm decisions.